Liberty Compared to Glyphosate Products in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
Postemergence treatments of Liberty (glufosinate) were compared to Durango DMA and Roundup PowerMax (glyphosate) after various preemergence treatments for efficacy in corn. Control of common sunflower, green foxtail, Russian thistle, and quinoa exceeded 92% regardless of herbicide treatment or evaluation date. Similarly, all preemergence (PRE) treatments controlled Palmer amaranth, kochia, and crabgrass by 93% or more. Later in the season, control of kochia was slightly less when Verdict (saflufenacil/dimethenamid) and atrazine PRE was followed by Roundup PowerMax and atrazine postemergence (POST). Palmer amaranth and crabgrass control was less when Verdict and atrazine PRE was followed by Roundup PowerMax or Liberty and atrazine POST. Herbicide treatments increased grain yields by 49–70% relative to the untreated controls.
Keywords: herbicide resistance